Perceptions of dietary intake amongst Black, Asian and other minority ethnic groups in high-income countries: a systematic review of qualitative literature - Abimbola S. Ojo; Lawrence A. Nnyanzi; Emma L. Giles; Louisa J. Ells; Olusegun Awolaran; Sylvester R. Okeke; Agani Afaya; Obasanjo Afolabi Bolarinwa (BMC Nutrition, 2023)
Abstract Background Minority ethnic groups are a fast-growing population in many high-income countries, partly due to the increasing population of immigrants and second-generation migrants. The dietary practices of some of these minority ethnic groups might make them to be disproportionately affected by obesity and increase their risks of developing non-communicable diseases. Population-specific interventions and strategies are vital to addressing poor nutritional practices among this population. Thus, this study systematically reviewed the perceptions of dietary intake amongst Black, Asian and other minority ethnic groups in high-income countries. Methods This systematic review was conducted in line with the guidelines of the Joanna Briggs Institute (JBI) methodology for systematic reviews, using a meta-aggregative design. This systematic review identified and synthesised qualitative literature on the perceptions of dietary intake amongst BlackAsian and other minority  ethnic groups in high-income countries. An extensive and comprehensive database search was conducted between January 2000 – May 2022 and included twenty (20) studies that met the eligibility criteria from six countries. The included studies were assessed for quality using the JBI qualitative assessment and review instrument. The JBI data extraction tools were used to retrieve relevant data from included articles, and the data were thematically analysed. Results We identified eight major themes across this database: (1) “Social and Cultural Factors,” (2) “Availability and Accessibility,” (3) “Family and Community Influences,” (4) “Food Preferences”, (5) “Home Country Food Versus Host Country Food” (6) “Dietary Acculturation” (7) “Health and Healthy Eating” (8) “Perception of Nutritional Information.” Conclusion Overall, Black, Asian, and other minority ethnic groups individuals were found to be aware of the effects of unhealthy eating on their health, and some of them have nutritional knowledge, but social and cultural factors, including structural factors, were deterrents to their healthy eating behaviours. An important finding from this review is that some participants believed that nutritional information, based on bio-medical science, was intended for only White population groups and that it was antagonistic to their cultural and community well-being.